Analysis Literacy Political Student in Context Citizenship Education Learning in Elementary Schools - Rahayu, Suci Mutia (International Journal of Students Education, 2025)
Civic education has a strategic role in developing political literacy of elementary school students through the formation of comprehensive civic competencies. This study aims to analyze the role of civic education in introducing the concept of responsible political participation to students, with a focus on the development of civic knowledge, civic skills, and civic disposition. The research method used is a literature study using a qualitative approach through a review of relevant journals and books from various scientific databases. The results of the study indicate that civic education plays an important role in shaping students’ political awareness through the transformation of democratic values and constructive political participation. The civic competencies developed include theoretical knowledge of the political system, critical thinking skills in decision-making, and the formation of moral character and responsibility as citizens. The conclusion of the study emphasizes the importance of integrating political education into the civic education curriculum since elementary school level. The development of sustainable political literacy is expected to form a young generation that is politically literate, democratic, and responsible. The research recommendation is the need for strengthening, habituation, and development of learning methods that can foster students’ political awareness through a contextual, participatory, and real-experience-based approach in community life.